Advances in accounting behavioral research. Vol. 9 - Arnold, Vicky (Advances in accounting behavioral research, 2006)
Volume 9 of Advances in Accounting Behavioral Research presents further empirical research in accounting theory. Its content is of wide appeal and crosses into the fields of applied psychology, sociology, management science, and economics. It presents empirical research in accounting theory.